2011
DOI: 10.4174/jkss.2011.81.1.35
|View full text |Cite
|
Sign up to set email alerts
|

An early single-center experience of portal vein thrombosis in living donor liver transplantation: clinical feature, management and outcome

Abstract: PurposePortal vein thrombosis (PVT) has been considered a relative contraindication for living donor liver transplantation (LDLT). However, it is no longer a contraindication of LDLT due to improvement in surgical techniques and approaches to PVT. The aim of this study was to assess the impact of PVT on outcomes in LDLT patients.MethodsWe retrospectively analyzed the data from 97 adult patients undergoing LDLT in our center from July 2008 to June 2010. Intraoperative findings and preoperative imaging results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
(35 reference statements)
0
16
1
Order By: Relevance
“…Two studies, in which LT was performed after 2000, compared the in-hospital survival between the LT recipients with and without PVT [28,37]. Both of them reported a statistically similar in-hospital survival between the two groups (95.5% versus 90.9%; 94.4% versus 96.2%).…”
Section: Survival In the Studies Where Lt Was Performed Before And Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, in which LT was performed after 2000, compared the in-hospital survival between the LT recipients with and without PVT [28,37]. Both of them reported a statistically similar in-hospital survival between the two groups (95.5% versus 90.9%; 94.4% versus 96.2%).…”
Section: Survival In the Studies Where Lt Was Performed Before And Afmentioning
confidence: 99%
“…Seven papers compared the in-hospital survival between the total LT recipients with and without PVT [16,18,27,28,37,39,41]. The heterogeneity was moderate (I虏=54.7%, P=0.04).…”
Section: Survival Of All Lt Recipients With Pvtmentioning
confidence: 99%
“…In the LDLT setting, there exist additional challenges in acquiring appropriate vein grafts, obtaining adequate portal flow, releasing portal hypertension, and preventing the development of small鈥恌or鈥恠ize syndrome. Few papers have reported a systematic strategy and LDLT outcomes for patients with PVT .…”
Section: Discussionmentioning
confidence: 99%
“…It is more difficult to find appropriate vein grafts and reconstruct the PV in living donor liver transplantations (LDLTs) than in DDLTs. Few papers have reported systematic strategies regarding LDLTs and outcomes in patients with PVT . Here, we introduce our current strategy of LDLT for PVT patients while considering the following factors: the extent/localization of the thrombus according to Yerdel's classification, hemodynamics, intraoperative control of PV pressure, and the postsurgical management of complications.…”
Section: Introductionmentioning
confidence: 99%
“…This led them to conclude that end-to-end CPHT might be a contraindication to adult LDLT with a hemiliver. In another article, Kim et al 10 reported their experience of 18 patients with PVT in a series of 97 LDLT recipients. No patient underwent CPHT in their series.…”
Section: Discussionmentioning
confidence: 99%